ASSESSMENT OF SMALLHOLDER FARMERS’ PREFERENCES AND UTILIZATION OF AGROFORESTRY TREE SPECIES IN KUDAN LGA, KADUNA STATE, NIGERIA - Daudu, C. K.; Adam, A. G.; Abdulshakur, M. M.; Olaifa, R. K.; Khalid, T. K. (Nigerian Journal of Agriculture and Agricultural Technology, 2026)
The study assessed farmers’ use of trees and agroforestry tree species preference among smallholder farmers in Kudan Local Government Area (LGA) of Kaduna State, Nigeria. A multistage sampling technique was employed to select 75 respondents, and data were collected using structured questionnaires. Descriptive statistics and multiple regression analysis were used for data analysis. The results revealed that 57.3% of the respondents were predominantly male, middle-aged (42.6%), and had low formal education, with inherited land tenure being the most common. Although awareness of government tree planting programmes was low (37.3%), more than half (54.7%) of the respondents had knowledge of agroforestry practices, mainly through extension agents (23.8%) and research institutes (19.0%). Fuelwood production (17.6%), soil fertility improvement (12.3%), and medicinal uses (10.8%) were the major benefits derived from trees. Indigenous tree species such as Khaya senegalensis (5.9%), Faidherbia albida (5.7%), Parkia biglobosa (5.0%) and Acacia senegal (5.2%) were the most preferred due to their multiple socio-economic and ecological benefits. Medicinal value (22.2%) and fuelwood (20.9%) needs were the primary reasons for tree species preference. Regression results showed that gender positively and significantly (0.418) influenced tree species preference, while family size had a negative significant effect (−0.195). Major constraints to agroforestry adoption included destruction of trees by animal herders (23.4%), pest infestation (23.4%), and charcoal-driven deforestation (19.1%). The study concludes that smallholder farmers in Kudan LGA have positive attitudes toward agroforestry, but adoption is constrained by institutional, ecological, and socio-economic factors. Strengthening extension services, addressing farmer–herder conflicts, and promoting access to improved tree seedlings are essential for enhancing agroforestry adoption.